EFEKTIVITAS WASTE TEA LEAVES (CAMELLIA SINENSIS) SEBAGAI BIO ADSORBEN PENYERAP LOGAM FE DAN PB DI SUNGAI MUSI PALEMBANG - Ayu, Selia Putri; Taufik, Muhammad (KINETIKA, 2021)
The Musi River is the main water source for the people of Palembang City which is utilized in various sectors such as fisheries, industry, transportation, and housing. These activities resulted in a decrease in the physical and chemical quality of the Musi River water which was marked by an increase in the concentration of heavy metals in it. Some of the polluting metals found in the water content of the Musi River are Fe and Pb. To reduce the levels of Fe and Pb, efforts are needed to bind them so that they are not mixed with river water. The purpose of this study was to determine the effectiveness of the use of tea waste as a bio adsorbent and to determine the level of metal reduction. The method used in this research is adsorption which is considered as a simple, effective, and can use adsorbents from unused materials. The adsorbent used was tea dregs waste with variations in the mass differences of the adsorbent of 0.25 grams, 0.50 grams and 0.75 grams and the contact time was 5 minutes, 10 minutes and 15 minutes. The research began with reducing the size of the tea dregs to 80 mesh, then chemical activation with 0.1 N HCl solution for Â± 24 hours. Furthermore, the adsorption process was carried out by contacting the adsorbent with the Musi River water sample based on the difference in time and adsorbent mass. The concentration of the adsorption solution was then analyzed using AAS. Based on the test results, the highest absorption of Fe that can be produced from tea dregs adsorbent is 80.78% in the adsorbent mass of 0.75 grams with a contact time of 15 minutes, while the highest absorption of Pb that can be produced from tea waste adsorbent is 93.75% in mass. adsorbent 0.75 grams with a turning time of 15 minutes.